PENGARUH MISMATCH DAN STRES KERJA TERHADAP KEPUASAN KERJA GURU MATA PELAJARAN SENI BUDAYA DI SMP DAN MTS SEKECAMATAN TAPUNG KABUPATEN KAMPAR - Sri Agustina Ratnawati (ENTINAS: Jurnal Pendidikan dan Teknologi Pembelajaran, 2024)
The aim of research (1) mismatch effect on job satisfaction (2) job stress effect on job satisfaction (3) mismatch dan job stress effect on job satisfaction together to teachers of art culture in junior high school and Islamic junior high school subdistrict Tapung Kampar district. Population of 60 teachers, end sampel 40 teachers the first do test instrumen to 20 responden. The validity of trial wear product moment and point basirial the while koefisien instrumen reliability. the instrumen be calculated with formula alpha cronbach. Test data analysis with korelasi pearson product moment. Acquisition of research results (1) there is a mismatch effect with job satisfaction the regression equations Ȳ=70,893+0,267 X1 (2) there is a job stress effect with job satisfaction the regression equations Ȳ=70,489+0,069 X2 (3) a significant difference between mismatch and job stress with job satisfaction teachers of art culture in junior high school and Islamic junior high school subdistrict Tapung Kampar district.the calculation result koefisien determinasi R2 yx1x2 = 0,917 amounting 91,7% through the regression Ȳ .